2016
DOI: 10.1139/cjas-2016-0096
|View full text |Cite
|
Sign up to set email alerts
|

Association between prolactin receptor gene polymorphism (PRLR) with reproduction performance traits of Polish swine

Abstract: The aim of this study was to estimate the relationship between prolactin receptor (PRLR) gene polymorphism and litter size in pigs of synthetic line 990 (n = 374). Prolactin receptor gene variants were determined by PCR-RFLP method. It was demonstrated that the analyzed polymorphism had significant influence (P ≤ 0.05) on reproduction traits in the first parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…However, later studies in various crossbreds and pure breeds have not always confirmed these results. Even though the same trend was obtained in most cases, a statistically significant difference was not always observed [ 7 , 8 ] or it was restricted to some parities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 55%
“…However, later studies in various crossbreds and pure breeds have not always confirmed these results. Even though the same trend was obtained in most cases, a statistically significant difference was not always observed [ 7 , 8 ] or it was restricted to some parities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 55%
“…The changes in target gene expression in endometrium further explain the mechanism underlying the different fetal survival rate during early gestation of LW and MS gilts. The RBP4 gene is a strong candidate to litter size in pigs by supplying vitamin A to the developing fetus ( Terman et al, 2011 ). Retinol would improve the uniformity of fetal size and the synchronism of development ( Bao et al, 2012 ) therefore improving the fetal survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Szyndler-Nędza et al (13) as well as Szyndler-Nędza et al (12) reported similar correlations and, in addition, determined a significant variability of reproduction indicators where AA homozygotes (locus MC4R) were characterised by a higher mean number of piglets born and reared up to day 21 of life in comparison with the remaining genotype sow groups. Terman et al (14) reported a strong polymorphic association in the MC4R locus with the total number of born piglets, number of piglets born alive (P ≤ 0.05, for litters 1 and 2) and the number of piglets reared up to day 21 (P ≤ 0.01, for litter 1) between sow genotype groups, with homozygotes recording higher results.…”
Section: Resultsmentioning
confidence: 98%